Disrupsi Akuntansi, Fase Titik Lejit Kemajuan Bisnis Dan Perekonomian - Rahayu, Siti Kurnia (Jurnal Riset Akuntansi dan Keuangan, 2021)
The Disruption phase is seen as a threat to the role of accounting in business and the economy. It is feared that accountants, accountants and auditors will be replaced by machines, so that work in the field of accounting will disappear in the future. This study aims to describe and explain cognitive understanding of the phenomena that occur, so that it can be used as a basis in the formulation of Long Life Learning Outcomes in the Field of Accounting based on the development of ICT in the Era of Disruption in Exponential Growth. The method used is a qualitative study, by conducting interviews with informants from graduate users and accountant professionals in Bandung, conducted in September to December 2019. Testing the data used was Triangulation Technique and data were analyzed inductively. The results showed that the Accounting Department can be a guardian in improving business and economic civilization through increased technical and soft skills in the Disruption Era. The research findings show that higher education accounting graduates are still lacking in soft skills compared to the ability of accounting and ICT techniques, so it is important to try to supply soft skills to prospective graduates.Fase Disrupsi dipandang sebagai ancaman pada peran akuntansi dalam bisnis dan perekonomian. Dikhawatirkan tenaga akuntan, akuntan dan auditor digantikan dengan mesin, sehingga pekerjaan di bidang akuntansi akan lenyap di masa depan. Penelitian ini bertujuan untuk menggambarkan dan menjelaskan pemaknaan secara kognitif mengenai fenomena yang terjadi, sehingga dapat dijadikan dasar di dalam perumusan Long Life Learning Outcomes di Bidang Akuntansi  berdasarkan perkembangan ICT dalam tahap Era Disruption pada Exponential Growth. Metode yang digunakan adalah Penelitian Kualitatif, dengan melakukan wawancara pada informan dari pengguna lulusan dan professional akuntan di Bandung, yang dilakukan pada Bulan September sampai Desember 2019. Pengujian data yang digunakan adalah Triangulation Technique dan data dianalisis secara induktif. Hasil penelitian menunjukkan bahwa Bidang Akuntansi dapat menjadi pengawal dalam peningkatan bisnis dan peradaban perekonomian melalui peningkatan technical skills maupun soft skills pada Era Disrupsi. Penemuan penelitian menunjukkan bahwa lulusan akuntansi Pendidikan Tinggi masih kurang dalam hal soft skills di banding kemampuan teknik akuntansi dan ICT, sehingga penting mengupayakan pembekalan soft skills pada calon lulusan.